Sangeet Swara: A Community-Moderated Voice Forum in Rural India - Vashistha, Aditya; Cutrell, Ed; Borriello, Gaetano; Thies, Bill (ACM - Association for Computing Machinery, 2015)
Interactive voice forums have emerged as a promising platform for people in developing regions to record and share audio messages using low-end mobile phones. However, one of the barriers to the scalability of voice forums is the process of screening and categorizing content, often done by a dedicated team of moderators. We present Sangeet Swara, a voice forum for songs and cultural content that relies on the community of callers to curate high-quality posts that are prioritized for playback to others. An 11-week deployment of Sangeet Swara found broad and impassioned usage, especially among visually impaired users. We also conducted a follow-up experiment, called Talent Hunt, that sought to reduce reliance on toll-free telephone lines. Together, our deployments span about 53,000 calls from 13,000 callers, who submitted 6,000 posts and 150,000 judgments of other content. Using a mixed-methods analysis of call logs, audio content, comparison with outside judges, and 204 automated phone surveys, we evaluate the user experience, the strengths and weaknesses of community moderation, financial sustainability, and the implications for future systems.
Best of CHI Award